Ministry of the Interior Decree No. 1777 of the Year 2023 On the Rules, Procedures, and Controls of Enforcing Prime Minister’s Decree No. 3326 of the year 2023 = وزارة الداخلية قرار رقم 1777 لسنة 2023 فى شأن قواعد وإجراءات وضوابط تنفيذ قرار رئيس مجلس الوزراء رقم 3326 لسنة 2023 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic